SISTEM INFORMASI RENTAL MOBIL BERBASIS WEBSITE PADA PUTRA JAYA RENTAL - Mira Adriyani (2022)
Putra Jaya Rental is one of the companies engaged in car rental services. The running system is ineffective because the recording and reporting process is still manual and prone to unwanted matter. Therefore, the researcher proposes a design for making a computerized car rental information system. The method in this study using the waterfall method. With data collection techniques using interviews and direct observation to the research site, system analysis using PIECES, system design using Unified Modeling System (UML), and the implementation phase using Black box testing. The result of this design is a website-based information system which can make it easier for users to get the information of available car, to do the transaction for rent the car and return, and make reports.